2016
DOI: 10.1038/srep21512
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic plutonium-244 in the environment: Insights into plutonium’s longest-lived isotope

Abstract: Owing to the rich history of heavy element production in the unique high flux reactors that operated at the Savannah River Site, USA (SRS) decades ago, trace quantities of plutonium with highly unique isotopic characteristics still persist today in the SRS terrestrial environment. Development of an effective sampling, processing, and analysis strategy enables detailed monitoring of the SRS environment, revealing plutonium isotopic compositions, e.g., 244Pu, that reflect the unique legacy of plutonium productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Neutron capture reactions resulting from the spontaneous fission of natural 238 U are also reported to generate naturogenic 239 Pu. 17,18 The fissile 239 Pu ( t 1/2 = 24 110 years) is the most common isotope formed by neutron capture from 238 U in typical nuclear power reactors, which further presents an energetic interest and enters into the composition of MOX (Mixed Oxide) fuel after separation and recycling steps. MOX is a ceramic made out of a mixture of depleted uranium and plutonium dioxides both crystallizing in the fluorite structure of the face-centered cubic system ( Fm 3̄ m space group).…”
Section: Introductionmentioning
confidence: 99%
“…Neutron capture reactions resulting from the spontaneous fission of natural 238 U are also reported to generate naturogenic 239 Pu. 17,18 The fissile 239 Pu ( t 1/2 = 24 110 years) is the most common isotope formed by neutron capture from 238 U in typical nuclear power reactors, which further presents an energetic interest and enters into the composition of MOX (Mixed Oxide) fuel after separation and recycling steps. MOX is a ceramic made out of a mixture of depleted uranium and plutonium dioxides both crystallizing in the fluorite structure of the face-centered cubic system ( Fm 3̄ m space group).…”
Section: Introductionmentioning
confidence: 99%
“…239 Pu is one of the three primary fissile isotopes synthesized the most ( 233 U and 235 U are the other two) [22]. In a reactor, more than 50% of 239 Pu will undergo fission, and a small part of it captures a neutron and produces 240 Pu, 241 Pu, 242 Pu, and 243 Pu [23]. The concentration of 239 Pu in nature is so small that its existence can be ignored.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although this radionuclide has been primarily known for its applications in astrophysics, anthropogenic 244 Pu could be an innovative tool due to the recently developed techniques to assess this radionuclide at environmental levels. 244 Pu can only be produced in thermonuclear explosions, where the fast neutron flux triggers its production after successive neutron capture reactions on 239 Pu. , Such processes are very unlikely in civil nuclear reactors due to the low neutron flux and the production of the short-lived 243 Pu ( t 1/2 = 4.956 h) by neutron capture of 242 Pu, which decays in the reactor before 244 Pu is produced. , This unique aspect of 244 Pu makes it ideal to differentiate Pu originating from thermonuclear explosions and other Pu sources, for example, fission weapon fallout and discharges from the nuclear fuel cycle. Several studies have been reported ,, establishing the first 244 Pu/ 239 Pu ratios for different sources (Table ).…”
Section: Introductionmentioning
confidence: 99%